Customer's satisfaction on logistics service quality provided by innovative e-commerce sites - MS. B. NEERAJA,; VENKATESH, MR. O.S. (The journal of contemporary issues in business and government, 2020)
The main aim of the study is to find out the customer satisfaction on logistics quality service of ecommerce. To provide valuable suggestions to the logistics and the e-commerce business to enhance the customer satisfaction, With the help of the real time data collected from students and employees by issuing questionnaires with the help of google forms. By getting the real time data we can easily predict the needs and wants of the customers. analyzing the data by working on SPSS software with various statistical tools. The results derived from this report will be useful from many e-commerce and logistics businesses. This study has been conducting By finding out the gap between customer satisfaction and logistics on e-commerce.